Law and property in Algeria : anthropological perspectives - Ben Hounet, Yazid. (Studies in the History and Society of the Maghrib, 2018)
In spite of its privileged place on the African continent, in the Muslim world and in the Middle East and North Africa region, Algeria remains poorly known, and the works relating to contemporary Algerian society published outside of Algeria are rare. This book seeks to contribute to our understanding of Algerian society today, through its relationships to property and to law. Beyond this, the objective is to propose, in a comparative perspective proper to anthropology, new theoretical and methodological perspectives by which to apprehend the anthropology of law in a Muslim context. Algeria, as a post-colonial and post-Socialist State, whose population is overwhelmingly Muslim, proves to be a particularly interesting case to study. Contributors are: Hichem Amichi, Emilie Barraud, Ammar Belhimer, Yazid Ben Hounet, Nejm Benessaiah, Sami Bouarfa, Tarik Dahou, Baudouin Dupret, Marcel Kuper, Judith Scheele, Alice Wilson.